Study on Treatment of 2,4,6-Trinitrotoluene Using Modified Red Mud - Van Huong, Nguyen; Son Tung, Pham; Thi Thuy Nguyen, Le; Van Manh, Nguyen; Thi Dieu Hanh, Nguyen; Manh Khai, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2025)
2,4,6-Trinitrotoluene (TNT) is a highly toxic and recalcitrant nitroaromatic organic compound, often originating from explosive manufacturing activities. In this study, red mud, a metal-oxide-rich waste product from alumina production, was modified by a thermal method at various temperature to enhance its adsorption capacity for TNT in water. SEM and XRD analyses showed that the red mud sample modified at 400 °C has a distinct granular structure and good adsorption capability. The results indicated that the modified material reached maximum adsorption capacity of 12.078 mg/g after being heated at 400 o C.  Under the conditions of pH = 3, a dosage of 1 g/100 mL of 50.0 mg/L TNT solution, and a reaction time of 60 minutes, the BT-400 sample achieved a TNT removal efficiency of 70.5%.